Social media trend analysis to predict the success of products using deep learning technique - Khan, Farden Ehsan; Ruhan, Ahmed Mahir; Shamsuddin, Rifat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.